A Standardized Procedure and Normative Values for Measuring Binocular Dynamic Visual Acuity. - Miskewicz-Zastrow, Amanda; Bishop, Eric; Zastrow, Alan; Cuevas, Dan Mark; Rainey, Bill B. (Optometry & Visual Performance, 2015)
Background: Binocular dynamic visual acuity (BDVA) is the ability to differentiate fine details in a moving object such as seams on a pitched baseball or the rotation of a tennis ball, both of which can travel up to speeds exceeding 100 miles per hour. BDVA is one of many binocular visual measurements to examine binocular function. This study was designed to provide a standardized procedure for measuring BDVA and normal values for a sample population. Previous studies have used different techniques for measurement, and thus have no normative data for comparison. Methods: The BCVA attachment to the Bernell Rotation Trainer was used to measure BDVA in 22 subjects (10 females and 12 males) between the ages of 23 and 30. Only subjects with a refractive error between +1.00 D and -7.00 D (spherical equivalent) and with bestcorrected visual acuity of 20/20 or better were able to participate in the study. BDVA was recorded at three different rotation speeds (29 RPM, 24 RPM, and 16 RPM). At each RPM, accuracy and the time to completion of all nine lines were measured. The subjects were also asked to complete a questionnaire designed to evaluate factors that may influence the BDVA results. Results: A decrease in RPM resulted in a corresponding decrease in the subject's completion time and an increase in accuracy. The same trend was seen when comparing males and females; however, the females' accuracy was lower and the time was greater when compared to the males, but these were not statistically significant. Conclusions: This was the first study designed to use the Bernell Rotation Trainer to quantitatively measure BDVA in a standardized way. Our results showed similar trends in both males and females. In addition, this study provides a strong foundation for future research, such as comparing BDVA of athletes and non-athletes, or comparing athletes with different skill levels, or comparing athletes who participate in different sports.